Ultrasensitive self-powered cytosensors based on exogenous redox-free enzyme biofuel cells as point-of-care tools for early cancer diagnosis. Issue 94 (7th October 2015) - Gai, Panpan; Song, Rongbin; Zhu, Cheng; Ji, Yusheng; Wang, Wengjing; Zhang, Jian-Rong; Zhu, Jun-Jie
Abstract : An exogenous redox-free, membraneless enzyme biofuel cell-based ultrasensitive self-powered cytosensor was constructed as a point-of-care tool for early diagnosis of cancer. Abstract : An exogenous redox-free, membrane-less enzyme biofuel cell-based ultrasensitive self-powered cytosensing platform was fabricated. With the ultrahigh sensitivity and the merits of not requiring external power sources or exogenous reagents, the device has great potential as a point-of-care tool for early diagnosis of cancer in vivo .